Mentoring in Tertiary Education in Nigeria - Ogunode, Niyi Jacob; Aisha, Haruna; Johnson, Ebute (Research Parks Publishers, 2023)
The sustainable development of the university system depends on an effective mentorship programme. Mentoring is the practical means of transferring of university culture, value, ethics and profession to the next generation. It is a way of ensuring that the university system maintains a particular standard and even improved. It is unfortunate that most universities’ mentoring programme In Nigeria is faced with a lot of problems. This paper looked at problems that has militated against the development of academic mentoring in the Nigerian universities. Secondary data were used in the paper and they were gathered from print publications and online journals. The paper identified lack of mentorship policy, strike Actions, poor funding, and inadequate attention from mentors, abuse of mentorship norms, lack of trust, poor communication, academic conflict and lack of freedom of mentees to express their ideas as problems that has militated against the development of mentorship programme in the universities in Nigeria. Based on these problems, the paper recommended that National Universities Commission should direct universities to institutionalization mentoring programme. Government should implement all agreement reached with different trade unions in the universities to prevent strike actions. Government should increase the funding of university education in Nigeria. National Universities Commission should organize workshops for senior academic on effective skills for mentorship in the universities. National Universities Commission should organize workshops for the junior lecturers (mentees) on mentoring processes and guide line for effective mentorship in the university system. This will help the mentees to learn the process of being mentored.